Arctic Freshwater Synthesis: Summary of key emerging issues. Issue 10 (3rd October 2015) - Prowse, T.; Bring, A.; Mård, J.; Carmack, E.; Holland, M.; Instanes, A.; Vihma, T.; Wrona, F. J.
Abstract: In response to a joint request from the World Climate Research Program's Climate and Cryosphere Project, the International Arctic Science Committee, and the Arctic Council's Arctic Monitoring and Assessment Program an updated scientific assessment has been conducted of the Arctic Freshwater System (AFS), entitled the Arctic Freshwater Synthesis ( AFS Σ ). The major reason behind the joint request was an increasing concern that changes to the AFS have produced, and could produce even greater, changes to biogeophysical and socioeconomic systems of special importance to northern residents and also produce extra‐Arctic climatic effects that will have global consequences. The AFS Σ was structured around six key thematic areas: atmosphere, oceans, terrestrial hydrology, terrestrial ecology, resources, and modeling, the review of each coauthored by an international group of scientists and published as separate manuscripts in this special issue of Journal of Geophysical Research‐Biogeosciences. This AFS Σ summary manuscript reviews key issues that emerged during the conduct of the synthesis, especially those that are cross‐thematic in nature, and identifies future research required to address such issues. Key Points: The domain of the Arctic Freshwater System is broader than previously thought New hydroecological regimes have developed in the Arctic Freshwater System New approaches are required to study changes in the Arctic Freshwater System